Stylistic And Political Issues In Donal J Trump’s Tweets - Ananda Hardianti Qamara; Sunardi; A.K Amarullah (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2021)
The study was considered as stylistics analysis because it was purposed to elaborate the features of graphological level and syntactic level that found in Trump’s tweets. In addition, it also discussed about the political issues that raised in his tweets because he was an active user of twitter since his presidency in 2017. This study was conducted at English Department Mulawarman University. The design of this study was qualitative approach which was purposed to classify the tweets into some features of graphological level and syntactic level. It was also used to classify the political issues raised within the tweets. There were found around 368 tweets between November 3rd and December 3rd, 2020. The instruments of the study were the writer herself and the tweets from Trump’s twitter. There were also found some tweets which were not contained the type of the levels and the political issues. Afterward, the data are collected from the tweets and have been triangulated. The first finding of the study indicated the features of graphological level. There were found some features such as full stop, comma, apostrophe, and others. Full stop was the feature of graphological level that was most frequently encountered. It has been detected approximately 614 times within the tweets. Additionally, at the syntactic level, it was discovered that the simple present tense was the most often used tense in the tweets. Trump's tweets contained the feature approximately 220 times. Then, in the following result, it was discovered that election related topics were the most frequently discussed political issues in tweets. During this same period, Trump has tweeted a lot about the electoral landscape. There were around 223 instances of it in the tweets.